Initiates - Gabbin, Joanne; McCray, Judith; Hodges, John L. (San Francisco, Calif. : California Newsreel, 1998)
Presenta los discursos de los poetas negros representantes de la literatura afroamerica de los años 90.
[Proclamadores]: Elizabeth Alexander, The dark room collective: Vera Beatty, Thomas Sayers Ellis, Major Jackson, John R. Keene, Sharan Strange, Natasha Trethewey, Kevin Young. -- VHS Hi-fi
Keywords: LITERATURA ESTADOUNIDENSE; POESIA; AUTORES AFROAMERICANOS; 1990-